2015
DOI: 10.1089/end.2014.0474
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Rendezvous Procedure for Ureteral Iatrogenic Detachment: Report of a Case Series with Long-Term Outcomes

Abstract: The endoscopic rendezvous procedure reduces the need for invasive open surgical repair and represents the optimal initial option in patients with iatrogenic ureteral lesions before invasive procedures with higher morbidity are attempted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The evaluation of this procedure after 3 months showed disappointing results. Perhaps a stent should have been maintained much longer to allow regeneration of the ureteral wall [6][7][8]. PN secured the kidney from damage.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of this procedure after 3 months showed disappointing results. Perhaps a stent should have been maintained much longer to allow regeneration of the ureteral wall [6][7][8]. PN secured the kidney from damage.…”
Section: Discussionmentioning
confidence: 99%
“…This technique entails advancing a catheter and wire through the ureteric gap to be captured from the opposite access using a snare or forceps under fluoroscopic or cystoscopic visualization. [ 2 4 5 6 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ureteric intussusception during retrograde introduction of double J stent was described in a previous case reported by Pastore et al . [ 6 ] This was managed by introducing the stent retrogradely. Strictures at the site of ureteric injury are commonly encountered due to the extra-anatomical passage of the stent and intense surrounding fibroblastic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…If stent placement is not possible following ureteral injury, placement of a percutaneous nephrostomy tube is required for renal drainage until elective repair can be accomplished. 1,[8][9][10] Several authors have reported reasonable rates of success with ureteroscopic ureteral realignment for iatrogenic ureteral injury during gynecologic and general surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…If stent placement is not possible following ureteral injury, placement of a percutaneous nephrostomy tube is required for renal drainage until elective repair can be accomplished. 1,[8][9][10] Several authors have reported reasonable rates of success with ureteroscopic ureteral realignment for iatrogenic ureteral injury during gynecologic and general surgical procedures. [9][10][11][12][13] However, to our knowledge, there has not been a previous report of successful endoscopic ureteral realignment following avulsion of the ureter at the level of the ureteropelvic junction.…”
Section: Introductionmentioning
confidence: 99%